The influence of physical activity during pregnancy on maternal, fetal or infant heart rate variability: a systematic review. Issue 1 (December 2016) - Dietz, Pavel; Watson, Estelle; Sattler, Matteo; Ruf, Wolfgang; Titze, Sylvia; van Poppel, Mireille
Abstract Background Physical activity (PA) during pregnancy has been shown to be associated with several positive effects for mother, fetus, and offspring. Heart rate variability (HRV) is a noninvasive and surrogate marker to determine fetal overall health and the development of fetal autonomic nervous system. In addition, it has been shown to be significantly influenced by maternal behavior. However, the influence of maternal PA on HRV has not yet been systematically reviewed. Therefore, the aim of this systematic review was to assess the influence of regular maternal PA on maternal, fetal or infant HRV. Methods A systematic literature search following a priori formulated criteria of studies that examined the influence of regular maternal PA (assessed for a minimum period of 6 weeks) on maternal, fetal or infant HRV was performed in the databases Pubmed and SPORTDiscus. Quality of each study was assessed using the standardized Quality Assessment Tool for Quantitative Studies (QATQS). Results Nine articles were included into the present systematic review: two intervention studies, one prospective longitudinal study, and six post-hoc analysis of subsets of the longitudinal study. Of these articles four referred to maternal HRV, five to fetal HRV, and one to infant HRV. The overall global rating for the standardized quality assessment of the articles was moderate to weak. The articles regarding the influence of maternal PA on maternal HRV indicated contrary results. Five of five articles regarding the influence of maternal PA on fetal HRV showed increases of fetal HRV on most parameters depending on maternal PA. The article referring to infant HRV (measured one month postnatal) showed an increased HRV. Conclusions Based on the current evidence available, our overall conclusion is that the hypothesis that maternal PA influences maternal HRV cannot be supported, but there is a trend that maternal PA might increase fetal and infant HRV (clinical conclusion). Therefore, we recommend that further, high quality studies addressing the influence of maternal PA on HRV should be performed (methodological conclusion).